Klinik und Genetik der hypertrophen und dilatativen Kardiomyopathie - Meder, Benjamin; Katus, Hugo (Der Internist, 2012)
Primary cardiomyopathies are frequent heart diseases with an estimated prevalence of 0.3-0.4% in the general population, significantly contributing to systolic heart failure and sudden cardiac death in the young. Molecular genetic studies have identified 49 different disease genes for hypertrophic and dilated cardiomyopathy, often involving proteins of the sarcomere, the cardiac Z-disc and the cytoskeleton. With the development of new, advanced technologies based on next-generation sequencing, it is now possible to efficiently screen all known disease genes in an individual patient.The clinical workup of cardiomyopathies should always include the investigation of the patient’s family to account for the familial aggregation of cardiomyopathies and identify diseased as well as asymptomatic carriers of mutations. The detection of specific genotypes facilitates diagnostic classification and can improve risk stratification in affected patients.
Paralleltitel von Frontdoor übernommen
Gesehen am 10.05.2019